PENGUATAN KERJASAMA KONTRA TERORISME INDONESIA-AMERIKA SERIKAT PADA TAHUN 2014-2018 - Samsuri Sirait; M. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research discuss about Indonesia’s interests in strengthening counter terrorism cooperation relations with the United States of America in effort to overcome the terrorism threat in Indonesia. Terrorism is the enemy of all nations and transnational in nature thus there is a need for various cooperation to eradicate it. The terrorism activity that have appeared both internationally and nationally throughout 2014 – 2018 have given quite a significant effect to Indonesia’s security stability. One of the nation that Indonesia have asked to cooperate in counter terrorism is the United States of America. Previous counter terrorism cooperation have convinced both nation to further strengthen this relation. The perspective used in this research is the Realism perspective based on the view that international cooperation is regarded as important if it’s goal is supporting the nation to achieve it’s interest. The theory used is the security theory. The focus of this research is to study Indonesia’s interest within the discourse of international terrorism. The data of this research is taken from books, journal articles, government documents, and websites.Indonesia in conducting counter terrorism cooperation strengthening with the United States of America to increase Indonesia’s security capability in overcoming terrorism. This was later proven by the increase in military assistance, training, and funding by the United State to Indonesia.Keywords: cooperation strengthening, counter terrorism, military, security